2017
DOI: 10.1038/s41598-017-16737-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pollen-mediated gene flow from glyphosate-resistant to -susceptible giant ragweed (Ambrosia trifida L.) under field conditions

Abstract: A field experiment was conducted to quantify pollen mediated gene flow (PMGF) from glyphosate-resistant (GR) to glyphosate-susceptible (GS) giant ragweed under simulated field conditions using glyphosate resistance as a selective marker. Field experiments were conducted in a concentric design with the GR giant ragweed pollen source planted in the center and GS giant ragweed pollen receptors surrounding the center in eight directional blocks at specified distances (between 0.1 and 35 m in cardinal and ordinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…Here, we accept our hypothesis as it was shown that under field research conditions mesotrione resistance alleles were transferred from R A. tuberculatus to S A. tuberculatus progeny through pollen. The frequency of gene flow was rapidly reduced within 45 m of the pollen source and varied with distance and direction, which was also documented with PMGF studies that used ALS (Liu et al ., ) and glyphosate resistance genes (Sosnoskie et al ., ; Ganie and Jhala, ; Sarangi et al ., ) in Amaranthus species. The mechanism of mesotrione resistance in R A. tuberculatus is herbicide detoxification via cytochrome P450 alleles (Oliveira et al ., 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we accept our hypothesis as it was shown that under field research conditions mesotrione resistance alleles were transferred from R A. tuberculatus to S A. tuberculatus progeny through pollen. The frequency of gene flow was rapidly reduced within 45 m of the pollen source and varied with distance and direction, which was also documented with PMGF studies that used ALS (Liu et al ., ) and glyphosate resistance genes (Sosnoskie et al ., ; Ganie and Jhala, ; Sarangi et al ., ) in Amaranthus species. The mechanism of mesotrione resistance in R A. tuberculatus is herbicide detoxification via cytochrome P450 alleles (Oliveira et al ., 2018c).…”
Section: Discussionmentioning
confidence: 99%
“…Gene flow frequency follows a binomial distribution with two possible outcomes in this study: yellow kernels (gene flow occurred) and white kernels (no gene flow occurred). The probability of gene flow is a function of the covariate, distance from pollen donor (Ganie & Jhala, 2017; Sarangi et al., 2017). Distance from the pollen donor can take on any real value; however, the probability of gene flow ranges between 0 and 1.…”
Section: Methodsmentioning
confidence: 99%
“…A set of 564 possible models was constructed to explain the frequency of gene flow using an exponential decay function with distance from the pollen donor, direction of the pollen receptor relative to the pollen donor, average wind speed, wind frequency, wind direction, and/or maximum wind gust (Ganie & Jhala, 2017; Sarangi et al., 2017). Additionally, models were evaluated with and without thresholds of air temperature, relative humidity, and the dual threshold of air temperature and relative humidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and a series of exponential decay models including wind parameters (speed, gust, and direction) were fitted to data for each nozzle × corn barrier combination using the gnm package in R Version 3.2.3 (R Foundation for Statistical Computing, Vienna, Austria). Akaike's information criterion (AIC) was used for the model selection, where the candidate model with the lowest AIC value was chosen to fit the data .…”
Section: Methodsmentioning
confidence: 99%